Comparative analysis of data protection regulations in East African countries - Shao, Deo; Ishengoma, Fredrick; Nikiforova, Anastasija; Swetu, Mrisho (Emerald, 2024)
Purpose Protection of personal data is integral to the digital economy, ensuring trust and privacy as its foundational elements. The purpose of this study is to analyze data protection laws in Tanzania, Kenya, Uganda and Rwanda to understand their legal frameworks and identify challenges hindering their effective implementation. Design/methodology/approach This study uses a comparative exploratory case study approach, analyzing legal frameworks of four East African (EA) countries through examination of legal documents, official reports and academic articles. The dimensions of analysis include registration, supervisory authority, data subject rights and cross-border data transfer regulations. Findings While all four EA countries are in the process of enacting data protection acts, they differ in scope, provisions and enforcement; more needs to be done to ensure mature data protection in these countries. The commonalities and distinctions in the legal frameworks are underscored, providing a mapping of data protection regulations in the EA region. Moreover, this study reports implementation constraints and areas for improvement. Practical implications The findings of this study provide valuable insights for policymakers, highlighting areas where data protection regulations can be improved. The results of this study can guide harmonizing regional data protection laws, ensuring consistent and effective enforcement. This study offers a foundation for future policy development and regional cooperation on data protection issues. Social implications The social implications of this research lie in its potential to shape public attitudes on data protection and privacy rights. By highlighting these concerns, this study may influence societal norms and values, encouraging a more informed and conscientious public discourse on inclusive policies that consider the diverse needs of different regional populations. Originality/value This study provides a pioneering comparative analysis of data protection regulations across four EA countries, offering unique insights into the regional variations and commonalities in legal frameworks. Its value lies in informing future policy development, enhancing regional cooperation and contributing to the harmonization of data protection practices in the selected EA countries, which remains an under-explored area in existing literature.